Retrieval of Simple Addition Facts: Complexities Involved in Addressing a Commonly Identified Mathematical Learning Difficulty - Hopkins, Sarah; Egeberg, Helen (Journal of learning disabilities, 2009)
There exists a substantial number of studies that have identified a subset of low-achieving mathematics students who do not develop a reliance on retrieval for simple addition but who continue to use a counting strategy to solve these problems. There are few studies, however, that have focused on how retrieval of simple addition facts may be improved. This study employed a combined methodological approach to examine the effect extended practice had on increasing a reliance on retrieval for simple addition. An intervention aimed at improving the efficiency of extended practice was also piloted. Although most students improved with extended practice, the extent of improvement was not practical for all students and the intervention did not generally improve the effectiveness of extended practice. The findings emphasize the critical importance of continuing such research and draw attention to the complexities involved in addressing retrieval difficulties for simple addition.